The answer is B) The transformation rule is (x, y) -> (x + 0, y + 4).
Answer:
x = 3 , y = 1
Step-by-step explanation:
2x + y = 7
3x + y = 8
solution
2x + y = 7-----------(1)
3x - y = 8------------(2)
from equation 1
2x + y = 7
y = 7 - 2x-------------(3)
substitute equation 3 into equation 2
3x - y = 8
3x - (7 - 2x) = 8
3x - 7 + 2x = 8
3x + 2x = 8 + 7
5x = 15
divide through by the coefficient of x
5x/5 = 15/5
x = 3
to find y
substitute x into equation 1
2x + y = 7
2(3) + y = 7
6 + y = 7
y = 7 - 6
y = 1
Answer:
p = <u>T</u> - a - <u>b</u>
Step-by-step explanation:
Hope that helps, not sure if it is correct though.
I have to admit I don't know what exactly you are asking, but I think this is it: 10m/s.
Divide m/s by time.
Answer:
105 pi m^2
Step-by-step explanation:
radius squared - radius squared =
(16+3)^2 - 16^2 =
19^2 - 16^2 =
361-256= 105